Analisis Masalah Belajar Matematika ABACUS - Somawati, Somawati (Indo-MathEdu Intellectuals Journal, 2024)
Abacus is a tool that teachers can use to solve math problems when they teach material about the greatest combination factors to students. This quantitative study aims to assess the difficulties faced by grade IV students at SD Negeri Kedungsukun Tegal during mathematics teaching with the ABACUS method. This study focused on 30 grade IV students at SD Negeri Kedungsukun Tegal. This study uses an experimental research design. Questionnaires are used to collect data. The data analysis technique in this study is simple regression analysis. The findings of the study revealed that the instructors were able to overcome problems that developed during the teaching of ABACUS mathematics in grade IV at SD Negeri Kedungsukun Tegal in the 2017/2018 school year. According to the conclusion of the study, the study was considered successful when the level of discipline reached 75%. Thus, problems in ABACUS mathematics teaching and learning can be overcome